Optimal Design of Sparse Matrix Phased Array Using Simulated Annealing for Volumetric Ultrasonic Imaging with Total Focusing Method; Sensors; Vol. 24, iss. 6 - Dolmatov D. O. Dmitry Olegovich (2024, 2024)
Title screen